Menghidupkan Kembali Legenda Jaka Tarub Animasi 2 Dimensi dengan Augmented Reality - Rachman, Anung; Kurniawan, Rendya Adi; Muslihah, Isnawati; Maharani, Aulira Iska (Universitas Informatika dan Bisnis Indonesia, 2024)
The article discusses the creation of 2D Jaka Tarub animation using Augmented Reality (AR) technology which aims to preserve local culture. Using qualitative literature study methods and a design thinking approach, this research explores the creative and technical processes in bringing back the story of Jaka Tarub through modern, interactive media. The results show AR technology provides new potential in enriching cultural narratives and connecting younger generations with Indonesia's traditional heritage. There are recommendations for further development in the field of cultural animation by utilizing AR technology and distribution strategies.